Amended diagnosis and redescription of Pristimantis marmoratus (Boulenger, 1900) (Amphibia: Craugastoridae), with a description of its advertisement call and notes on its breeding ecology and phylogenetic relationships - Kok, Philippe J.R.; Dezfoulian, Raheleh; Means, D. Bruce; Fouquet, Antoine; Barrio-Amorós, César L. (European Journal of Taxonomy, 2018)
The frog Pristimantis marmoratus was originally described as Hylodes marmoratus by George A. Boulenger in 1900 based on a single specimen reported to have been collected at the foot of Mount Roraima in Guyana in 1898. We herein discuss the exact location of the type locality of P. marmoratus and provide a redescription of the species based on new material from Kaieteur National Park and from the slopes of Maringma-tepui in Guyana. We also describe the previously unknown vocalization and breeding ecology of the species, and conducted an exploratory molecular analysis of the phylogenetic relationships within the genus Pristimantis represented by the members of the “unistrigatus species group” in the Guiana Shield. Pristimantis marmoratus is a small-sized species mainly distinguished from its known Guiana Shield congeners by the combination of F I < II, SVL ≤ 20.4 in males, presence of vocal slits in males, granular/pustulate dorsal skin with well-developed scapular ridges, basal webbing between fingers, fringes on fingers and toes, crossed iris, diffuse yellow or pale green wash on groin, and absence of flashy colour on axillary/pre-axillary region. The advertisement call consists of a single note repeated at a rate of ca 11 calls/min with a dominant frequency ranging from 2756 to 3101 Hz. Pristimantis marmoratus is primarily arboreal, exclusively active at dusk, and probably restricted to the pristine rainforests of the Pantepui uplands and highlands, east of the Gran Sabana between ca 600 and 1800 m above sea level. Preliminary molecular analyses recovered Pristimantis marmoratus as sister to an unnamed species from the Eastern Guiana Shield. On grounds of the newly established distributional extent we suggest maintaining the IUCN conservation status as Least Concern.